Clinical validation of ratings on the six-item Positive and Negative Syndrome Scale obtained via the Simplified Negative and Positive Symptoms Interview. (September 2021) - Kølbæk, Pernille; Dines, David; Holm, Tine; Blicher, Anne B; Sørensen, Rune D; O'Leary, Kathrine M; Feller, Sandra G; Buus, Chanette W; Nielsen, Cecilie M; Opler, Mark; Mors, Ole; Correll, Christoph U; et al.
Background: The six-item version of the Positive and Negative Syndrome Scale (PANSS-6) has shown promise as a brief measure of the severity of core symptoms of schizophrenia. However, since all prior analyses of the PANSS-6 were based on data extracted from studies using the full 30-item PANSS (PANSS-30), it remains unknown whether it is possible to obtain valid information for the PANSS-6 ratings via a brief interview, such as the Simplified Negative and Positive Symptoms Interview (SNAPSI). Aims: We aimed to validate the PANSS-6 ratings obtained via the SNAPSI using the PANSS-6 scores extracted from the PANSS-30 ratings obtained via the comprehensive Structured Clinical Interview for PANSS (SCI-PANSS) as the gold-standard reference. Methods: The PANSS-6 ratings based on the SNAPSI and the PANSS-30 ratings based on the SCI-PANSS were conducted by independent raters with established inter-rater reliability. Results: Seventy-seven inpatients with schizophrenia ( M age = 35.1 ± 11.7 years; males = 57%; paranoid schizophrenia = 75%) participated in the study. The intraclass correlation coefficient (ICC) of the PANSS-6 total scores obtained using the SNAPSI and the PANSS-30-derived PANSS-6 total scores via the SCI-PANSS was 0.77 ( p < 0.001). The ICC for the PANSS-6 total score and the PANSS-30-derived PANSS-8 (Andreasen's remission criteria) was 0.75 ( p < 0.001). Spearman's rank correlation coefficient for changes in PANSS-6 total scores via the SNAPSI and changes in PANSS-30-derived PANSS-6 total scores was 0.70 ( p < 0.001). Conclusions: Using the SNAPSI to rate the PANSS-6 enables a focused and brief assessment of the severity of core symptoms of schizophrenia, which facilitates measurement-based care and clinical decision making in the treatment of schizophrenia.